2016
DOI: 10.3390/ijms17020156
|View full text |Cite
|
Sign up to set email alerts
|

miR-16-5p Is a Stably-Expressed Housekeeping MicroRNA in Breast Cancer Tissues from Primary Tumors and from Metastatic Sites

Abstract: For quantitative microRNA analyses in formalin-fixed paraffin-embedded (FFPE) tissue, expression levels have to be normalized to endogenous controls. To investigate the most stably-expressed microRNAs in breast cancer and its surrounding tissue, we used tumor samples from primary tumors and from metastatic sites. MiRNA profiling using TaqMan® Array Human MicroRNA Cards, enabling quantification of 754 unique human miRNAs, was performed in FFPE specimens from 58 patients with metastatic breast cancer. Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Without a consensus about the ideal reference gene to study miRNA expression in plasma, we opted for miR‐16‐5p because it has been demonstrated to be stably expressed in plasma of several different mouse strains at different ages and disease conditions (Mi et al , ). Moreover, Rinnerthaler et al () have demonstrated that miR‐16‐5p is also stably expressed in breast cancer tissues, both from primary and metastatic sites, indicating that it is a good housekeeping gene for our study, which was further confirmed by qPCR data. qPCR results (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Without a consensus about the ideal reference gene to study miRNA expression in plasma, we opted for miR‐16‐5p because it has been demonstrated to be stably expressed in plasma of several different mouse strains at different ages and disease conditions (Mi et al , ). Moreover, Rinnerthaler et al () have demonstrated that miR‐16‐5p is also stably expressed in breast cancer tissues, both from primary and metastatic sites, indicating that it is a good housekeeping gene for our study, which was further confirmed by qPCR data. qPCR results (Fig.…”
Section: Resultssupporting
confidence: 75%
“…The qRT-PCR was performed using a Bio-Rad CFX Connect Real-time System (Bio-Rad), with the threshold cycle number determined by Bio-Rad CFX manager software V.3.0. mRNA expression was normalized to HPRT (29) and miRNA expression was normalized to miR-16-5p (30,31). The following primers were used for PCR analysis: miR-196b-5p 5′‑TAGGTAGTTTCCTGTTGTTGGG‑′3 (sense) and 5′‑GCGAGCACAGAATTAATACGAC‑′3 (anti-sense), miR-16-5p 5′-TAGCAGCACGTAAATATTGGCG‑′3 (sense), 5′‑GCGAGCACAGAATTAATACGAC‑′3 (anti-sense), HOXA10 5′‑ AGATATTGTCCTAAGTGTCAAGTCCTGA‑′3 (sense), 5′‑GCCATTTCGAGCAGTGGG‑′3(anti-sense), TFF1 5′‑GGTCCTGGTGTCCATGCTG‑′3 (sense), 5′‑ACAGCAGCCCTTATTTGCAC‑′3(anti-sense).…”
Section: Methodsmentioning
confidence: 99%
“…In undifferentiated P19 cells, miR-126 can damage actin fibers and maintain microtubular stability (Rinnerthaler et al 2016), and it can reduce Cdc42 protein level and affect the intracellular localization of Rac1 through the Rho GTPase family, thereby influencing axonal growth . As a microRNA potentially inhibiting the malignant progression of glioma, miR-126 may affect its motility and migration through cytoskeleton-associated proteins.…”
Section: Introductionmentioning
confidence: 99%